2022
DOI: 10.3233/jad-220246
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Proteomics Reveals Significant Changes in Relation to Alzheimer’s Disease and Aging

Abstract: Background: Aging is a risk factor for several pathologies as Alzheimer’s disease (AD). Great interest exists, therefore, in discovering diagnostic biomarkers and indicators discriminating biological aging and health status. To this aim, omic investigations of biological matrices, as saliva, whose sampling is easy and non-invasive, offer great potential. Objective: Investigate the salivary proteome through a statistical comparison of the proteomic data by several approaches to highlight quali-/quantitative var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 77 publications
5
19
0
Order By: Relevance
“…RF analysis, one of several up-to-date machine learning methods, evidenced a panel of proteins/peptides present in saliva able to correctly classify PBCp group with respect to HCs with an 83.3% accuracy, AIHp group with respect to HCs with an 79.9% accuracy and PBCp with respect to AIHp with an 80.2% accuracy. The same statistical approach has been successfully used to classify groups of subjects based on age and health status highlighting the feasibility of the salivary proteome to discriminate groups of subjects based on physiological or pathological condition not only confined to oral cavity [ 75 ]. RF results were confirmed by LDA which provided a very good classification of subject based on PBC or AIH occurrence and with respect to HCs.…”
Section: Discussionmentioning
confidence: 99%
“…RF analysis, one of several up-to-date machine learning methods, evidenced a panel of proteins/peptides present in saliva able to correctly classify PBCp group with respect to HCs with an 83.3% accuracy, AIHp group with respect to HCs with an 79.9% accuracy and PBCp with respect to AIHp with an 80.2% accuracy. The same statistical approach has been successfully used to classify groups of subjects based on age and health status highlighting the feasibility of the salivary proteome to discriminate groups of subjects based on physiological or pathological condition not only confined to oral cavity [ 75 ]. RF results were confirmed by LDA which provided a very good classification of subject based on PBC or AIH occurrence and with respect to HCs.…”
Section: Discussionmentioning
confidence: 99%
“…This explorative proteomic study, based on an AP-MS approach, was inspired by the results that we obtained in previous top-down proteomic investigations on the salivary proteome associated with Alzheimer’s disease. We previously demonstrated that some salivary proteins/peptides, including S-modified proteoforms of cystatin B, significantly varied in abundance between AD patients and healthy controls [ 14 , 15 ]. Due to the relevance of developing proteomic studies in peripheral biofluids to the AD-associated biomarker discovery and the known ability of cystatin B to interact in multi-protein complexes [ 24 , 25 , 26 , 27 ] and considering the significance of PPI studies in the field of neurodegenerative disease, we decided to investigate the possible PPI of cystatin B in AD saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Altered levels of cystatin B have been observed in the context of AD, where high amounts of the protein were found post-mortem in the brains of patients [ 13 ]. Our recent studies on the salivary proteome in AD patients evidenced significantly higher levels of cystatin B compared to age-matched elderly healthy individuals [ 14 , 15 ], suggesting the existence of a self-protection mechanism in the patients, which could reflect the neuronal protective role of cystatin B in the brain [ 14 , 15 ]. AD is the most common neurodegenerative disease (ND) afflicting the elderly population, and its principal hallmarks are misfolded beta-amyloid (Aβ) and tau proteins in the central nervous system (CNS) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations